2019
DOI: 10.1038/s41431-019-0420-7
|View full text |Cite|
|
Sign up to set email alerts
|

gr/gr deletion predisposes to testicular germ cell tumour independently from altered spermatogenesis: results from the largest European study

Abstract: The association between impaired spermatogenesis and TGCT has stimulated research on shared genetic factors. Y chromosome-linked partial AZFc deletions predispose to oligozoospermia and were also studied in TGCT patients with controversial results. In the largest study reporting the association between gr/gr deletion and TGCT, sperm parameters were unknown. Hence, it remains to be established whether this genetic defect truly represents a common genetic link between TGCT and impaired sperm production. Our aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This has been seen in the development of gonadoblastoma in Turner's syndrome patients (81) as well in other germ cell tumors in patients with disorders of sexual development (82). The previously discussed gr/gr deletion has been implicated in the development of testicular germ cell tumors (83,84). Beyond the testicle, loss of the Y chromosome in peripheral blood has been found to be a risk factor for the development of colorectal and prostate cancer (85).…”
Section: Y Chromosome Copy Number Variation-beyond Infertilitymentioning
confidence: 94%
“…This has been seen in the development of gonadoblastoma in Turner's syndrome patients (81) as well in other germ cell tumors in patients with disorders of sexual development (82). The previously discussed gr/gr deletion has been implicated in the development of testicular germ cell tumors (83,84). Beyond the testicle, loss of the Y chromosome in peripheral blood has been found to be a risk factor for the development of colorectal and prostate cancer (85).…”
Section: Y Chromosome Copy Number Variation-beyond Infertilitymentioning
confidence: 94%
“… 64 Partial AZFc (gr/gr) deletions may also predispose men to testicular germ cell tumors, particularly in normospermic carriers. 65 Screening for partial AZFc deletions, such as gr/gr, may help prevent these negative clinical outcomes at little additional cost. This practice may be particularly beneficial in certain populations (ie Spanish and Italian men), in which previous research has consistently shown associations between gr/gr and infertility.…”
Section: Partial Azfc Deletions and Duplicationsmentioning
confidence: 99%
“…DAZ family DAZ: case-control studies of gr/gr men find increased relative risk of GCT (Moreno-Mendoza et al, 2019;Nathanson et al, 2005). DAZL: GWAS (Ruark et al, 2013).…”
Section: Germ Cell Commitment and Gonadal Developmentmentioning
confidence: 99%
“…De novo structural rearrangements of the Y chromosome regularly affect DAZ copy number and are a significant cause of spermatogenic failure (Rozen et al, 2012). One common Y-chromosome rearrangement, the gr/gr deletion, removes two copies of DAZ and is associated with an elevated GCT risk, particularly in men with a family history of GCTs (Moreno-Mendoza et al, 2019;Nathanson et al, 2005;Repping et al, 2003). Furthermore, the autosomal gene DAZL is directly implicated in the heritability of GCTs by GWAS (Ruark et al, 2013).…”
Section: Differentiation Of the Somatic Gonad Instructs Germ Cell Commitmentmentioning
confidence: 99%